FIZJONOMIA I UKŁADY URBANISTYCZNE NOWEGO BUDOWNICTWA MIESZKANIOWEGO JAKO ELEMENT KSZTAŁTOWANIA WARUNKÓW MIESZKANIOWYCH (NA WYBRANYCH PRZYKŁADACH) - Milewska-Osiecka, Katarzyna (Space – Society – Economy, 2011)
Since the 1970s, the dominant form of residence in the Polish cities has been buildings that were homogeneous in their form and a spatial layout scheme. It has been criticized not only for visual reasons. This resulted in a phenomenon of almost total breakdown of social relationships in the housing unit areas. Dehumanisation of housing, weakening personal interactions, and an increase in risk caused a significant decrease of housing conditions. The programme of the socialist transformation of the country assumed creating similar housing conditions for all citizens. Newly built housing units were an example of the functional monotony, with scarcity of architectural forms, lack of green areas and services. These conditions were favourable for violating the neighbourly coexistence rules, hooligan’s behaviour, as well as a decline in mutual recognition and personal safety. The beginning of the transformation process in Poland has caused fundamental changes in operating conditions and the role of housing. Recently constructed housing objects have begun to take varied forms. Nowadays, as far as housing is concerned, there seem to be two dominant phenomena: creating small, isolated housing composition layouts, and the formation of gated communities. New spatial and architectural standards, referring to both, the building blocks and their location on the building plot, as well as the elements of small architecture allow to create peculiar ‘estate in estate’ − small enclaves in the areas already partially developed, and in those of the early stages of development process. Buildings are located so that they create the inner yards (with playgrounds, green areas, car-parks). This way shaped space is supposed to be more easily tamed by its residents, stimulate creating housing communities, and cause greater concern for the surrounding areas. Residential settlements are characterised by smaller scale than in was in the in the 1960’s−1980’s. This applies to both, the number of buildings and the size of houses, which are much smaller, better adjusted to the human scale. The manifestation of the changes is the emergence of closed housing estates or buildings. The common denominator of all such objects is the spatial isolation. However, the physical barrier does not strengthen identification with the place of residence. Polish housing is at a stage of huge technological transformation which results in physiognomic changes. The houses built from prefabricated elements are characterised by simple forms with only few details. It is more and more common that buildings are ‘revived’ by a great variety of colours and materials, as well as by leaving flat roofs behind. The greatest potential for shaping the physiognomy of buildings is in the use of conventional or mixed technology. Newly built houses are characterised by simple forms and high aesthetics based on attention to details. The contemporary residential space changes according to the principles of the capitalist formation. It means that it is considerably shaped by economic criteria – those relating to the demand and the supply of housing and residential areas, as well as to the social factors (with the fundamental question: where and how we live?). Accommodation not only is a desirable good from the economic point of view, but also it is valuable as far as the social criteria are concerned, since it is seen as one of the indicators of social position.